Preparing health students for interprofessional placements. (March 2016) - Grace, Sandra; McLeod, Gopi; Streckfuss, Julie; Ingram, Lissa; Morgan, Annette
Abstract: Clinical education increasingly includes opportunities for interprofessional (IP) placements but few opportunities for students and supervisors to adequately prepare for such placements. The aim of this project was to further develop and evaluate an online multidisciplinary resource that was originally designed to prepare students for single-discipline placements. The revised resource aimed to prepare health students and their supervisors for IP placements. The resource was trialled in host organisations with participants from naturopathy, nursing, osteopathy and pharmacy. The resource used language that was common to all participants and comprised activities that had broad relevance such as orientating students to specific placements, developing learning plans, clarifying roles, rights and responsibilities, and clinical scenarios that raised ethical and professional issues. The effectiveness of the resource as an IP learning tool was evaluated using an E-survey, focus groups and feedback from the project team. According to participants, the resource afforded insights into what other disciplines do and opportunities for cross-disciplinary interactions, which helped break down stereotypes and misconceptions. Cross-disciplinary commonalities such as those pertaining to patient care, communication and ethics became evident. Collaborative projects involving academics, clinical supervisors and students from multiple disciplines provided an opportunity for culture change in an education organisation from single discipline to a more collaborative interdisciplinary one. Highlights: Health students and supervisors have little preparation for interprofessional placements. An IP online resource that used language and scenarios relevant to all health disciplines was developed and trialled. Resources to prepare students and supervisors for interprofessional placements were shared across disciplines. Online discussion forums facilitated cross-disciplinary interactions. Collaborative projects involving multiple professions can effectivley promote an IP culture.